Akal dan Agama Perempuan (Perspektif Hadis Nabi dan Psikologi)
This article is a reinterpretation of the meaning of Hadith with the interconnection-integration paradigm, focused on the study of the Hadith about women's reason and religion through psychological approach. In the Hadith, Rasulullah stated that most of the inhabitants of hell are women, their minds are less (na>qis